Mitigating the impact of trans-spectral processes on multivariate retrieval of water quality parameters from case 2 waters - Bukata, Robert P; Jerome, John H; Borstad, Gary A; Brown, Leslie N; Gower, James F.R (Canadian journal of remote sensing, 2004)
This work considers the impact of inelastic trans-spectral processes (Raman scattering and fluorescence from chlorophyll and dissolved organic matter) in terms of their impacts on estimating water quality information from remote sensing of inland and coastal (case 2) waters. Well-known results from studies of the contributions of trans-spectral processes to subsurface volume reflectance and water-leaving radiance are briefly reviewed and discussed. A means of mitigating their impact on bio-optical models currently in use and previously developed for optically complex waters (without deliberation of inelastic processes per se) is suggested in terms of the manner in which the inherent optical properties (optical cross section spectra) required for their use are determined. In situ determinations of volume reflectance are consequences of all elastic and inelastic processes occurring within the water column. Hence, values of the local inherent optical properties determined in situ already incorporate impacts of trans-spectral processes. Therefore, remotely sensing natural waters whose pertinent optical cross section spectra were determined in situ would not be subject to the same degree of retrieval uncertainty as remotely sensing waters whose pertinent optical cross-section spectra were determined under controlled laboratory conditions. Expansion of the currently meager catalogue of field-acquired optical cross section data, therefore, is once again strongly endorsed.